Perilaku Konsumen dalam Berbelanja Online dimasa Pandemik Covid-19 - Titi Herawati; Muhammad Iqbal Fasa; Suharto (Scimadly Publishing, 2022)
To meet their daily needs for goods and services, people need to look for other good alternatives to make shopping easier. So that people start using e-commerce in the trade of goods and services so that everyone can access it. The purpose of this study is to find out how consumer behavior in online shopping is, then how to implement it in the midst of the Covid-19 pandemic. This research was conducted using descriptive qualitative research methods from journals and resumes from previous studies. The results show that by applying consumer behavior when shopping online will give a good impression to buyers and sellers. Consumer behavior must also reflect their relationship with Allah in accordance with the teachings of the Qur'an, so that humans are not wasteful in making purchases to meet the needs of each individual.